Stress cardiac MRI for the evaluation of CCS patients in a real-world tertiary care center. (14th October 2021) - Busi, G; Fumagalli, C; Vannini, M; Pontecorboli, G; Pradella, S; Acquafresca, M; Marchionni, N; Valenti, R; Carrabba, N
Abstract: Background: The MR INFORM trial demonstrated that myocardial perfusion Magnetic Resonance Imaging (MRI) is non-inferior to Invasive Coronary Angiography (ICA) with measurement of Fractional Flow Reserve (FFR) in guiding the management of patients with stable coronary artery disease with respect to major adverse cardiac events, despite a reduced rate of revascularized patients. We sought to evaluate if a MRI-based strategy performed well also in patients with Chronic Coronary Syndrome (CCS) with intermediate coronary plaques observed by Coronary Computed Tomography Angiography (CCTA). Methods: At our tertiary care center, patients with suspicion of CCS at intermediate risk first underwent CCTA. Subsequently, those showing intermediate coronary plaques underwent dipyridamole stress cardiac MRI. Revascularization was recommended for patients showing ischemia in at least two consecutive left ventricular segments or 6% of the myocardium. ICA and instantaneous FFR was performed in all of these patients, in order to confirm the indication for revascularization. The endpoint was a composite of death, non-fatal myocardial infarction, and target-vessel revascularization within 1 year. Results: 55 patients at intermediate risk underwent CCTA. 15 patients with no or only minimal plaques (stenosis <30%) and those with obstructive plaques (stenosis >70%) were excluded. 40 patients showed intermediate plaques (30–70% stenosis): 102 plaques total were classified as: non calcified n=9 (9%), calcified n=48 (47%), and mixed n=45 (44%). These patients underwent stress MRI, on the basis of which n=12 (30%) patients met criteria to recommend revascularization, whereas n=28 (70%) did not. The indication for revascularization was confirmed by ICA plus iFFR in 10 patients, and excluded in 2 (sensitivity = 100%, 95% CI 69%-100%; specificity = 93%, 95% CI 78%-99%; NPV = 100%, 95% CI 88%-100%; PPV = 83%, 95% CI 57%-95%; accuracy = 95%, 95% CI 83%-99%). Revascularization was obtained through PCI in 9 patients and through CABG in the remaining patient. All patients, regardless of revascularization, received optimal medical therapy (OMT), including high-dose statins. Throughout a 1-year follow-up, the composite endpoint occurred in only 1 patient belonging to the revascularized group, who was admitted to our hospital for NSTEMI. No adverse events were observed among the negative-MRI patients and the positive-MRI not-revascularized patients. All patients remained free from angina. Conclusions: According to current European guidelines, in our tertiary care center patients with CCS at intermediate risk first underwent CCTA. A stress MRI-based strategy for the evaluation of intermediate plaques led us to refine the selection of patients needing coronary revascularization. No events occurred in patients with negative MRI, highlighting the accuracy of CCTA plus stress MRI strategy in these patients. In all patients, OMT may have contributed to freedom from angina. Funding Acknowledgement: Type of funding sources: None.